find the zeroes of the polynomial root 3x square+10x+7 rpot 3 and verify the relationship between zeroes ans their coefficients
Answers
Answered by
258
p(x) = √3x2+10x+7√3
= √3x+3x+7x+7√3
= (√3x+7)(x+√3)
= √3x+7 = 0 and x+√3 = 0
= x = -7/√3 and x = -√3
verification by α and β,
let α = -7/√3 and β = -√3
sum of zeros = α+β = -7/√3+(-√3)
= -7/√3-√3
= -7-3/√3
= -10/√3
product of zeroes = αβ
= -7/√3 . -√3
= 7.
verification by coefficients,
sum of zeros = -b/a
= -10/√3.
product of zeros ,
= c/a
= 7√3/√3
= 7.
hence relationship is verified.
= √3x+3x+7x+7√3
= (√3x+7)(x+√3)
= √3x+7 = 0 and x+√3 = 0
= x = -7/√3 and x = -√3
verification by α and β,
let α = -7/√3 and β = -√3
sum of zeros = α+β = -7/√3+(-√3)
= -7/√3-√3
= -7-3/√3
= -10/√3
product of zeroes = αβ
= -7/√3 . -√3
= 7.
verification by coefficients,
sum of zeros = -b/a
= -10/√3.
product of zeros ,
= c/a
= 7√3/√3
= 7.
hence relationship is verified.
Answered by
286
Hello dear...
Solution here ..✌✌
________________________
Let the given Polynomial be denoted by f(x) . Than ,
![f(x) = \sqrt{3} {x}^{2} + 10x + 7 \sqrt{3} \\ = > \sqrt{3} {x}^{2} + 3x + 7x + 7 \sqrt{3} \\ = > \sqrt{3}x(x + \sqrt{3} ) + 7(x + \sqrt{3} ) \\ = > (x + \sqrt{3} )( \sqrt{3} x + 7) \\ \\ f(x) = 0 \\ \\ = > (x + \sqrt{3} ) = 0 \: \: or \: \: ( \sqrt{3} x + 7) = 0 \\ = > x = - \sqrt{3} \: \: \: \: \: \: \: \: and \: \: x = \frac{ - 7}{ \sqrt{3} } f(x) = \sqrt{3} {x}^{2} + 10x + 7 \sqrt{3} \\ = > \sqrt{3} {x}^{2} + 3x + 7x + 7 \sqrt{3} \\ = > \sqrt{3}x(x + \sqrt{3} ) + 7(x + \sqrt{3} ) \\ = > (x + \sqrt{3} )( \sqrt{3} x + 7) \\ \\ f(x) = 0 \\ \\ = > (x + \sqrt{3} ) = 0 \: \: or \: \: ( \sqrt{3} x + 7) = 0 \\ = > x = - \sqrt{3} \: \: \: \: \: \: \: \: and \: \: x = \frac{ - 7}{ \sqrt{3} }](https://tex.z-dn.net/?f=f%28x%29+%3D++%5Csqrt%7B3%7D++%7Bx%7D%5E%7B2%7D++%2B+10x+%2B+7+%5Csqrt%7B3%7D++%5C%5C++%3D++%26gt%3B++%5Csqrt%7B3%7D++%7Bx%7D%5E%7B2%7D++%2B+3x+%2B+7x+%2B+7+%5Csqrt%7B3%7D++%5C%5C++%3D++%26gt%3B++%5Csqrt%7B3%7Dx%28x+%2B++%5Csqrt%7B3%7D+%29+%2B+7%28x+%2B++%5Csqrt%7B3%7D+%29+%5C%5C++%3D++%26gt%3B+%28x+%2B++%5Csqrt%7B3%7D+%29%28+%5Csqrt%7B3%7D+x+%2B+7%29+%5C%5C++%5C%5C+f%28x%29+%3D+0+%5C%5C++%5C%5C++%3D++%26gt%3B+%28x+%2B++%5Csqrt%7B3%7D+%29+%3D+0+%5C%3A++%5C%3A+or+%5C%3A++%5C%3A+%28+%5Csqrt%7B3%7D+x+%2B+7%29+%3D+0+%5C%5C++%3D++%26gt%3B+x+%3D++-++%5Csqrt%7B3%7D++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+and+%5C%3A++%5C%3A+x+%3D+++%5Cfrac%7B+-+7%7D%7B+%5Csqrt%7B3%7D+%7D+)
so the zeros of f (x) are -√3 and -7/√3
We have to verify
-------------------------------------
![sum \: \: of \: zeros \: = ( - \sqrt{3} + \frac{ - 7}{ \sqrt{3} } ) = \frac{ - 10}{ \sqrt{3} } = \frac{coefficient \: \: of \: x)}{coefficiet \: \: of \: {x}^{2} } \\ \\ product \: \: of \: zeros = \frac{ - 7}{ \sqrt{3} } \times - \sqrt{3} = 7 = \frac{constant \: \: term}{coefficient \: \: of \: {x}^{2} } sum \: \: of \: zeros \: = ( - \sqrt{3} + \frac{ - 7}{ \sqrt{3} } ) = \frac{ - 10}{ \sqrt{3} } = \frac{coefficient \: \: of \: x)}{coefficiet \: \: of \: {x}^{2} } \\ \\ product \: \: of \: zeros = \frac{ - 7}{ \sqrt{3} } \times - \sqrt{3} = 7 = \frac{constant \: \: term}{coefficient \: \: of \: {x}^{2} }](https://tex.z-dn.net/?f=sum+%5C%3A++%5C%3A+of+%5C%3A+zeros+%5C%3A++%3D++%28+-++%5Csqrt%7B3%7D+++%2B++%5Cfrac%7B+-+7%7D%7B+%5Csqrt%7B3%7D+%7D+%29+%3D++%5Cfrac%7B+-+10%7D%7B+%5Csqrt%7B3%7D+%7D++%3D++%5Cfrac%7Bcoefficient+%5C%3A++%5C%3A+of+%5C%3A+x%29%7D%7Bcoefficiet+%5C%3A++%5C%3A+of+%5C%3A++%7Bx%7D%5E%7B2%7D+%7D++%5C%5C++%5C%5C+product+%5C%3A++%5C%3A+of+%5C%3A+zeros+%3D++%5Cfrac%7B+-+7%7D%7B+%5Csqrt%7B3%7D+%7D++%5Ctimes++-++%5Csqrt%7B3%7D++%3D+7+%3D++%5Cfrac%7Bconstant+%5C%3A++%5C%3A+term%7D%7Bcoefficient+%5C%3A++%5C%3A+of+%5C%3A++%7Bx%7D%5E%7B2%7D+%7D+)
Hence verified ..
______________________________
Hope it's helps you.
☺☺
Solution here ..✌✌
________________________
Let the given Polynomial be denoted by f(x) . Than ,
so the zeros of f (x) are -√3 and -7/√3
We have to verify
-------------------------------------
Hence verified ..
______________________________
Hope it's helps you.
☺☺
Similar questions